DIGITAL INNOVATION IMPLEMENTATION TO PREVENTS INCIDENT CASE USING REAL TIME iCCTV MONITORING SYSTEM WITH CHANGE & CONFLICT MANAGEMENT APPROACH (Case Study PT. CSOC*) (The Indonesian Journal of Business Administration, 2020)
Central Sumatera Oil Company (CSOC) is a subsidiary of one of the world’s leading integrated energy companies, which also lead the Indonesia national oil production for many decades with 25 – 30% of total country daily production. With the vision of “to be the global energy company most admired for its people, partnership and performance”, CSOC always want to be at the forefront for production and innovation. iCCTV is one of the CSOC forefront innovation that bring up safety to another level of implementation to prevent incident case in B&R rig operation. This project was started in early of 2019 and believed to be the pioneer to others team in CSOC operation and in the future to be implement in others business unit or even other companies.By collecting information during field interviews with constructing a Research Design Questions, some root causes were analyzed as the causal factor of main problem why the performance of online iCCTV was not too effective at the beginning of implementation through fishbone diagram analysis. With signal issue and punishment /accountability model issue were believed as most contributing factors to be solve in order to boost of the number of online iCCTV in B&R rig operation. The change management with Kotter’s 8 step innovative changes approach and conflict management by Thomas & Kilmann approach were used to create solutions on the issues arises. The result of implementing correct change management and conflict management approach were able to bring the online iCCTV status from average of 25 – 35% to 50 – 60% in order to reach the goal which being set by the B&R management at the beginning of the project. Later in the end of this research, due to Covid-19 pandemic, the implementation of iCCTV was being upgraded, not only for safety monitoring but also used as a tool to perform remote supervision to solve the shortage of manpower issue in B&R rig Operation. Keywords: rig, CCTV, change management, conflict management